2016
DOI: 10.1002/hbm.23428
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in practice-dependent resting-state functional connectivity related to motor sequence learning

Abstract: Decreased neural plasticity is observed with healthy ageing in the primary sensorimotor (SM1) cortex thought to participate in motor learning and memory consolidation processes. In the present magnetoencephalography study, the post-training reorganization of resting-state functional connectivity (rsFC) and its relation with motor learning and early consolidation in 14 young (19-30 years) and 14 old (66-70 years) healthy participants were investigated. At the behavioral level, participants were trained on a mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 82 publications
(152 reference statements)
8
54
1
Order By: Relevance
“…It is conceivable that increased connectivity could not be manifested within the 20 min of SES, which may explain why activity rather than connectivity correlated with skill acquisition on day 1. In addition, the present data reinforce the importance of the ␤ frequency range in visuomotor learning processes (Mary et al 2017;Veldman et al 2018;Wu et al 2014). Available data suggest that the ␤-frequency range-much more than other frequency ranges-may reflect interactions between sensory and motor cortices, and even with muscle spindle afferents, thereby providing further evidence that SES can be used to target the motor system (Baker 2007).…”
Section: Neurophysiological Mechanisms Underlying Ses-improved Skill supporting
confidence: 81%
See 1 more Smart Citation
“…It is conceivable that increased connectivity could not be manifested within the 20 min of SES, which may explain why activity rather than connectivity correlated with skill acquisition on day 1. In addition, the present data reinforce the importance of the ␤ frequency range in visuomotor learning processes (Mary et al 2017;Veldman et al 2018;Wu et al 2014). Available data suggest that the ␤-frequency range-much more than other frequency ranges-may reflect interactions between sensory and motor cortices, and even with muscle spindle afferents, thereby providing further evidence that SES can be used to target the motor system (Baker 2007).…”
Section: Neurophysiological Mechanisms Underlying Ses-improved Skill supporting
confidence: 81%
“…We measured activity in sensorimotor areas reflected by the N30 somatosensory evoked potential (SEP) that is sensitive to changes in motor performance following skill learning (Andrew et al 2015;Rossi et al 2003) and also quantified interregional connectivity by the phase slope index (PSI). Previous studies showed that the magnitude of connectivity correlated with motor learning (Mary et al 2017;Mehrkanoon et al 2016;Veldman et al 2018;Wu et al 2014). The PSI estimates not only the magnitude, but also the direction of effective connectivity by quantifying the dependence of phase lag between two signals on frequency.…”
Section: Introductionmentioning
confidence: 94%
“…Twenty-five young (12 females and 13 males; age: 23.6 ± 2.9 years (mean ± standard deviation); age range: 19–31 years) and twenty-five elderly (15 females and 10 males; 68.8 ± 2.4 years; age range: 65–74 years) healthy adult subjects were included in this study. Of notice, resting-state MEG data from fifteen of the twenty-five elders were already used in previous studies from our group 63 , 64 . All participants were right-handed according to the Edinburgh handedness questionnaire (laterality scores young: 76.4 ± 15.2; laterality scores old: 89.2 ± 13.4), had no prior history of neurological or psychiatric disorder, and did not report of any subjective sleep or cognitive (e.g., memory impairment) problem.…”
Section: Methodsmentioning
confidence: 99%
“…For clinical factors, tumor location in the right and left, or motordominant and non-dominant hemisphere, could also introduce variability (Volkmann et al, 1998;Jung et al, 2003;Pool et al, 2014), although no influence was observed here and in our previous studies (Nagarajan et al, 2008). Furthermore, aging is associated with changes in motor beta ERD, as well as a decrease in motor cortical plasticity, and might be a source of reorganization itself (Rossiter et al, 2014;Mary et al, 2017;Rueda-Delgado et al, 2019). It is also possible that the biological manifestation of motor cortical network reorganization in our cohorts could arise from a signal to noise difference in network activation, perhaps superimposed upon the effects observed here.…”
Section: Sources Of Variability That Contribute To Brain Reorganizationmentioning
confidence: 67%